Understand and care - Meiners, Cheri J., 1957-; Johnson, Meredith (Minneapolis, MN : Free Spirit Pub. Inc., 2003)
Explores how one can understand other people's feelings and how to be a good friend to someone who is feeling happy or sad.
Keywords: Empathy -- Juvenile literature; Sympathy -- Juvenile literature; Conduct of life; Emotions; Empathy; Sympathy